Impact of sodium-glucose cotransporter-2 inhibitors on aging biomarkers and plasma ceramide levels in type 2 diabetes: beyond glycemic control - Youssef M. Shalaby; Mohammed Moutaz Nakhal; Bachar Afandi; Bashar Al-Zohily; Lina Majed; Kukkala Kiran Kumar; Bright Starling Emerald; Bassem Sadek; Amal Akour; Nadia Akawi (Annals of Medicine)
Background Aging is a complex biological process marked by the decline of physiological functions and heightened susceptibility to chronic illnesses, notably cardiometabolic disorders. Ceramides (Cer) are lipid derivatives linked to aging and metabolic diseases. Sodium-Glucose Cotransporter-2 inhibitors (SGLT2i), widely used in managing type 2 diabetes, have an unclear impact on aging biomarkers and Cer profiles.Objective This study explored the association between SGLT2i use, plasma Cer levels (CerC16:0, CerC18:0, CerC22:0, CerC24:0, and CerC24:1), and aging biomarkers—Human Insulin-Like Growth Factor 1 (IGF-1), mammalian target of rapamycin (mTOR), 5-Methylcytosine (5MC), and Human H2AFX (Histone H2AX) in patients with type 2 diabetes mellitus (T2DM).Methods In this retrospective study, 95 participants were divided into three groups: patients on SGLT2i (n = 34), patients on non-SGLT2i anti-diabetic treatments (n = 36), and healthy controls (n = 25). Plasma Cer and aging biomarkers were quantified using Liquid Chromatography with tandem mass spectrometry (LC–MS–MS) and ELISA, respectively. Principal component analysis (PCA) assessed group-based clustering, while ANCOVA evaluated group differences with confounder adjustment.Results SGLT2i-treated patients showed significantly lower CerC16:0, CerC22:0, and CerC24:1 levels (p < 0.01) and decreased 5MC and H2AX (p < 0.05) compared to non-SGLT2i patients. IGF-1 was significantly elevated in the SGLT2i group (p < 0.01), suggesting a possible protective effect on metabolic health. PCA distinguished control from diabetic groups but revealed overlap between SGLT2i and non-SGLT2i groups.Conclusion Beyond glucose control, SGLT2i may improve plasma Cer and aging markers in diabetic patients, supporting their broader therapeutic potential in aging and age-related diseases. Further large-scale studies are warranted to confirm these effects and underlying mechanisms.